A model for adoption of successive generations of a high technology product. (5th December 2006) - Bardhan, Amit Kumar; Chanda, Udayan
Modelling the new product sales growth and forecasting future sales has been an important area of research in Marketing Science. Models have been proposed to map the consumer buying behaviour against explanatory variables such as price, promotional effort, quality, time, etc. In comparison, high technology products have received less attention. These products usually have many generations, each succeeding generation being an improvement over the previous one. This paper discusses some well-known models in this area and also proposes a new one. The new model uses the relationship between the repeat purchasers and the new purchasers in the overall diffusion of a new technology over multiple generations, by separately identifying the two types of adopters. This model has been validated on sales-data and has also been compared to an established model.